Transparent, predictable and enforceable working conditions: when the right to information on automated systems becomes an instrument of collective protection - Giuseppe Antonio Recchia (Labour & Law Issues, 2023)
The recent decision of the Employment Tribunal of Palermo, recognising the anti-union nature of the refusal of a food delivery platform to provide information on the automated systems used in the relationship with its riders, offers the cue to reflect on Article 1-bis of Legislative Decree No. 152/1997, introduced by Legislative Decree No. 104/2022, and on the relationship between individual and collective information rights. Finally, the article offers some reflections on the amendments made to the Article 1-bis by the so-called Work Decree of May 2023.